Analisis Keterampilan Menulis Cerita Pendek pada Siswa Kelas Fase C - Rizky Junior Efendi; Heny Kusuma Widyaningrum; Cerianing Putri Pratiwi (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2024)
Writing is a process of expressing ideas through written media, one of which is a short story, which is a story that has a light conflict and is easy to resolve. This study aims to analyze the ability to write short stories in phase C grade students at Dimong 03 Elementary School. This study uses a qualitative descriptive approach. There are four assessment aspects that must be understood by students, namely the completeness of the formal aspects of the short story, the completeness of the intrinsic elements of the short story, the integration of the short story structure, and the appropriateness of the use of short story language. The results of the study showed differences in writing abilities between students. Based on the analysis of the four assessment aspects, all students calculated the average value (83%), the short story writing ability of grade V students at SDN Dimong 03 as a whole was categorized as